THE EFFECT OF USING THE SHOW AND TELL (S&T) METHOD ON STUDENT’s ENGLISH VOCABULARY MASTERY AT SMP AL-WASHLIYAH 24 MEDAN - Santi Humairoh; Teguh Satria Amin (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to prove that using the show and tell method is more effective than traditional methods for teaching vocabulary to second-year students at SMP Al Washliyah 24 Medan during the 2022/2023 academic year. The study employed a quantitative methodology and it was classified as experimental research with a control group. The population for this research consists of four classes, with a total sample size of 70 students. The utilization of cluster random sampling and observation of two classes were the choosen methods for this study by the researchers. The researcher selected VIII-1 and VIII-2 as the experimental and controlled classes, each consisting of 35 students. Based on the analysis of the mean score gap in the post-test between the experimental and controlled classes, it can be concluded that the technique used was effective. The mean score of the experimental class was significantly higher at 9.02 compared to the controlled class which had a mean score of 5.63. This indicates that the experimental class had a better understanding of the subject matter, and the technique used in the experiment was successful in improving their performance. It can be concluded that The Show & Tell (S&T) Method is effective in improving student’s vocabulary mastery